The Effect of Central Government Expenditure (Capital and Goods Expenditure, and Social Assistance Spending) on Gross Regional Domestic Product of Provincial Government, 2014-2019 - Widodo, Slamet (Jurnal Budget : Isu dan Masalah Keuangan Negara, 2020)
In order to carry out concurrent government affairs in regional level, the central government allocates spending to support investment growth in the regions through capital expenditure, goods expenditure and social assistance spending. This capital accumulation is intended to increase the output of local government goods and services which in turn will increase regional economic growth. The purpose of this study is to analyze the Impact of Central Governmet Expenditure (Capital, Goods, and Social Assistance Expenditures) towards Gross Regional Domestic Product (PDRB) of provincial government for the period of 2014-2019. The data used was taken from BPS, the Ministry of Finance, and other relevant agencies. Analysis tools using data panel regression with fixed effect model. The results of the analysis shows that only capital expenditure has positive effect on PDRB, and social assistance expenditure has negative effect on PDRB. While goods expenditure variable is excluded from the model since it not met the multicollinearity test.